Areal Quantification Changes Assessment in Ibn Najm Marsh(southern Iraq) Using Multitemporal, Multisptial and Multispectral Satellite Images - Al-baldawi, Sabah; khtan, Asraa; Harba, Hind. (Iraqi Journal of Science, 2024)
Iraq has had more than 10000 km2 of geographical low land areas called marshes.Enriched with great diversity of natural vegetation and wild life. With increasingclimatic changes and passive man interference phenomena, vast areas of thesemarshes have deteriorated through drying out processes at an alarming rate.According to recent survey achieved by several Iraqi ministries marshes areas havedecreased to about quarter of theS original area. The statistical data and geospatialinformation are weak. We monitored, assessed the environmental processes anddetect changes using digitally processed landsat MSS (Multispectral Scanner) andSpot (System Pour Observation) satellite images that transform haur Ibn Najm(marsh) into agricultural land as result of desiccation processes. Seasonal and longtermchanges are detected. Hydrological and terrain changes are studied .Themethodology of using multitemporal , multispatial and multispectral images iscurrently being evaluated in this marsh ,by using land sat MSS data with (79x79m)spatial resolution and spot data with (10x10m) spatial resolution , acquired between1985 and 2002 respectively. The area of haur Ibn Najm has been calculated in bothimages before and after drying out processes according to GIS (Geographicinformation System) .Ground truth points have been plotted in the previous marshor present cultivated land by GPS (Global Positioning System) to support theindisputable facts reached.